ADAB FOR A PEACEFUL WORLD: A Study of Jalaluddin Rumi’s Concept of Sufism - Maurisa Zinira (Teosofia: Indonesian Journal of Islamic Mysticism, 2016)
Rumi’s spiritual teaching is slightly different from others' in a way that his devotional concepts put greater emphasis on ethics. Rumi believes that spirituality tightly relates to ethics, without which one neither could attain nor be able to stay in spiritual perfection. To sail to God, one should implement some ethical values best covered by the frame to love and to renunciate. To love entails loving God and His creatures, while to renunciate indicates the detachment from worldly desires. Putting these two into application, one will be able to attain the union with the Sublime Being (fana’). However for Rumi, one could be said to reach spiritual perfection only after he returned from self-mortification and gained spiritual wisdom that allows him to share universal love to the rest of human lives (baqa’).